2003
DOI: 10.1002/ajim.10236
|View full text |Cite
|
Sign up to set email alerts
|

Exposure assessment for study of olfactory function in workers exposed to styrene in the reinforced‐plastics industry

Abstract: This quantitative exposure evaluation has provided a well-characterized population, with documented exposure histories stable over time and in the range suitable for the purposes of the associated study of olfactory function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 17 publications
(23 reference statements)
2
5
0
Order By: Relevance
“…Study details and results are presented in Table 14. Styrene exposures were fairly consistent with the data reported for similar processes by Lees et al (2003). Use of respiratory protection was associated with higher blood and air styrene concentrations, consistent with greater use of respiratory protection among the more highly exposed workers.…”
Section: Occupational Exposuressupporting
confidence: 86%
See 3 more Smart Citations
“…Study details and results are presented in Table 14. Styrene exposures were fairly consistent with the data reported for similar processes by Lees et al (2003). Use of respiratory protection was associated with higher blood and air styrene concentrations, consistent with greater use of respiratory protection among the more highly exposed workers.…”
Section: Occupational Exposuressupporting
confidence: 86%
“…Some studies or reviews reported data indicating that generally styrene exposures have tended to decrease over time (Pfäffli and Säämänen, 1993;Welp et al, 1996;Macaluso et al, 2004). However, styrene exposures in the reinforced plastic facilities as reported by Lemasters et al (1985a) were essentially similar to the exposure levels reported by Lees et al (2003) and Luderer et al (2004). Based on the reported exposure range (3-82 ppm), a daily respiratory rate of 10 m 3 at work, and a 70-kg body weight, nominal daily styrene intake in the reinforced plastic industry is estimated at 2-51 mg/kg bw/day.…”
Section: Summary Of Human Exposure Datasupporting
confidence: 72%
See 2 more Smart Citations
“…Despite the improvement of work practices, ventilation systems, and personal protection measures, there was still some overexposure observed in this industry: in 31% of cases, the TWA concentration exceeded the German threshold limit value of 20 ppm. Lees et al (2003) assessed the styrene exposure of 52 persons employed in four American factories making reinforced plastics. Their mean 8 h TWA respiratorcorrected annual average styrene exposure was 12.6 ppm.…”
Section: Styrene Exposure In Industrymentioning
confidence: 99%